Degree of Disorders of Calcium-Phosphorus Maintenance in Children with Food Allergy Signs Depending on Allergic Inflammation Activity - L.S. Ovcharenko; A.O. Vertehel; T.H. Andrienko; I.V. Samokhin; N.V. Zhikhareva; O.V. Kriazhev (Zaslavsky O.Yu., 2015)
37 % of children aged from 1 to 3 years old have impairment in various parameters associated with food allergy. These changes are typical for osteogenesis (reduced concentration of general calcium by 15.7 %, non-organic phosphorus - by 17.8 %, enhanced activity of alkaline phosphatase - by 89.8 %, blood serum osteocalcin - 4.4 times (Р < 0.05)). The presence and activity of persistent chronic allergic inflammation in children with food allergic is one of the reasons of impaired osteogenesis that is confirmed by direct and inverse relations between allergic inflammation factors (extension, skin dryness, burning sensation, skin flaking) and osteogenesis markers (general calcium, non-organic phosphorus, alkaline phosphatase, parathyroid hormone, osteocalcin) (ρ = -0.884; -0.765; +0.884; -0.651; +0.803; relatively). The key factor causing impaired osteogenesis in children with food allergy is an extension (kS > 40) of allergic process on skin that has a direct correlation with severity of metabolism impairment in bone tissue (ρ = +0.820).